Brief Report: Soluble CD163 in CMV-Infected and CMV-Uninfected Subjects on Virologically Suppressive Antiretroviral Therapy in the ICONA Cohort. (1st March 2017) - Vita, Serena; Lichtner, Miriam; Marchetti, Giulia; Mascia, Claudia; Merlini, Esther; Cicconi, Paola; Vullo, Vincenzo; Viale, Pierluigi; Costantini, Andrea; D'Arminio Monforte, Antonella
Abstract : Aims: To contribute to the understanding of the role played by cytomegalovirus (CMV) in sustaining monocyte/macrophage-mediated immune activation in antiretroviral therapy treated HIV-infected subjects. Design and Methods: We selected 23 CMV-uninfected and 46 CMV-infected HIV+ subjects, matched for age, CD4 nadir, HIV infection duration, and viral hepatitis serostatus. All subjects were on successful antiretroviral therapy since at least 1 year. A group of 16 healthy donors with similar age and sex was also included. Plasma levels of tumor necrosis factor–alpha, interleukin-6, sCD163, sCD14, and CMV immunoglobulin G levels were measured in duplicate with human enzyme-linked immunosorbent assay kits. Results: We found significantly higher sCD163 plasma levels in HIV+CMV+ compared with HIV+CMV− subjects and healthy donors. This augmentation was confirmed also when subjects positive for hepatitis C virus–Ab were excluded from analysis. Interestingly, a correlation between anti-CMV immunoglobulin G levels and sCD163, tumor necrosis factor–alpha, interleukin-6, and sCD14 in HIV+CMV+ subjects was found. Conclusions: CMV coinfection could be a major driver of monocyte/macrophage activation in virally suppressed HIV+ individuals and might explain the increased risk of non-AIDS morbidity/mortality in HIV/CMV-coinfected subjects.